2015
DOI: 10.1186/s13024-015-0056-1
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of aquaporin-4 in APP/PS1 mice exacerbates brain Aβ accumulation and memory deficits

Abstract: BackgroundPreventing or reducing amyloid-beta (Aβ) accumulation in the brain is an important therapeutic strategy for Alzheimer’s disease (AD). Recent studies showed that the water channel aquaporin-4 (AQP4) mediates soluble Aβ clearance from the brain parenchyma along the paravascular pathway. However the direct evidence for roles of AQP4 in the pathophysiology of AD remains absent.ResultsHere, we reported that the deletion of AQP4 exacerbated cognitive deficits of 12-moth old APP/PS1 mice, with increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
328
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 363 publications
(356 citation statements)
references
References 64 publications
21
328
2
5
Order By: Relevance
“…For example, the water channel AQP-4, predominantly expressed in the end-feet of astrocytes, regulates A␤ accumulation, cerebral amyloid angiopathy, and synapses in APP/PS1 mice . Of note, deletion of AQP-4 has been shown to increase astrocyte atrophy and suppresses LRP1 expression in the astrocytes surrounding A␤ plaques (Yang et al, 2012;Xu et al, 2015). Our results showed that deletion of LRP1 in the astrocytes did not significantly alter the levels of AQP-4, suggesting that AQP-4 may function in the upstream of LRP1 in astrocytes.…”
Section: Lrp1 Ligand Rap (mentioning
confidence: 45%
“…For example, the water channel AQP-4, predominantly expressed in the end-feet of astrocytes, regulates A␤ accumulation, cerebral amyloid angiopathy, and synapses in APP/PS1 mice . Of note, deletion of AQP-4 has been shown to increase astrocyte atrophy and suppresses LRP1 expression in the astrocytes surrounding A␤ plaques (Yang et al, 2012;Xu et al, 2015). Our results showed that deletion of LRP1 in the astrocytes did not significantly alter the levels of AQP-4, suggesting that AQP-4 may function in the upstream of LRP1 in astrocytes.…”
Section: Lrp1 Ligand Rap (mentioning
confidence: 45%
“…This suggests that unknown abluminal mechanisms may be involved in perivascular AQP4 localization. Mislocalization of AQP4 at the astrocyte endfoot has also been confirmed in several mouse models of AD (32, 65, 66). To further extrapolate the role of perivascular AQP4 localization, a study using the same model of VaD as described above in rats, found that decreased perivascular AQP4 expression persisted up to 6 weeks after microinfarction(30).…”
Section: Glymphatic Systemmentioning
confidence: 67%
“…Interestingly, Aqp4 gene deletion reduced Aβ42-induced astrocyte activation, in vitro (Yang et al, 2012). Recently, it was shown that deletion of Aqp4 in the APP/PS1 mice exacerbates Aβ accumulation in brain and contributes to memory deficits (Xu et al, 2015). Our data are congruent with these studies, but also indicated that soluble Aβ oligomers, a more toxic form of Aβ, may contribute to the suppression of glymphatic activities in aging APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%